The Theater in 2010 (XXI Century. Spanish Literature and Culture, 2012)
The work begins with a general summary of theater shows produced in Spain during 2010. It also deals with the year’s most important openings, examining both classical and modern-day productions, in addition to adaptations of works by foreign authors.
Keywords: theater; Spanish theater 2010; criticism; representation; production